(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2011)
Criticism of the new system of pre-trial detention (flagrante and preventive) is beginning to mount. From July 4th, when Law 12.403 comes into force, criminal proceedings could change the face of the judiciary. Preliminary assessments indicate that around 100,000 prisoners will be released immediately. For some, the law will make it impossible to order pre-trial detention, allowing perpetrators of serious crimes to remain free during the process. What’s more - and this is no small feat - they curse the innovative precautionary measures, which are emerging as alternatives to imprisonment before the final conviction. The state - these critics argue - won’t be able to monitor them. In short, the crowning of impunity in Brazil!